UiTM world obesity day program 2023 - Md Yasin, Mazapuspavina; Tharek, Zahirah; Abdul Malek, Khasnur; Nik Mohd Nasir, Nik Munirah; Kamaruddin, Khairatul Nainey; Lohshini Kanoo, Lina; Ismail, Ilham Ameera (Faculty of Medicine, 2023)
UiTM's Weight Management Clinic (WMC/Obesity Clinic) and the Department of Primary Medicine (PCM) UiTM organized a UiTM World Obesity Day (WOD) 2023 program at HASA UiTM between 13 March to 17 March 2023, supported by Al-Sultan Abdullah Hospital (HASA), with Professor Dr. Sazzli Shahlan Kasim as the Director and Faculty of Medicine (FOM) UiTM Sg Buloh Campus with Prof Fazah Akhtar Hanapiah as the Dean. This program was in conjunction with the World Obesity Federation (WOF) celebration of WOD on 4 March 2023.